(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Hyperbilirubinemia is a common problem in newborn. Most of the cases are benign but severe hyperbilirubinemia can lead to kernicterus and brain damage which is preventable. The gold standard to asses neonatal hyperbilirubinaemia is serum bilirubin measurement. Unfortunately, this procedure is invasive, painful and time consuming. As the consequence of missing severe hyperbilirubinemia is serious, there is a constant search to find out a safe method to detect jaundice. Transcutaneous bilirubinometry offers objective method of assessing degree of jaundice reducing subjectivity of clinical assessment. Objective: To evaluate the relationship between transcutaneous bilirubin (TcB) and total serum bilirubin (TSB) and assess whether transcutaneous bilirubinometry can be used as a valid screening method for detecting jaundice in term and late preterm babies. Method: A prospective cross-sectional study was performed in well baby nursery of United Hospital Limited, Dhaka from January 2013 to December 2013. Healthy term and late pre term newborn of ?35 wk gestation with clinical evidence of jaundice were included in the study. Total serum bilirubin was measured by Dichlorophenyl Diazonin method and transcutaneous bilirubinometer (JM-103) was used to measure transcutaneous bilirubin (TcB) level. Result: A total of 116 paired samples were analyzed and found strong correlation between TcB and TSB (correlation coefficient 0.8, mean difference 0.83, SD± 1.96 and 95% CI 0.6 to 1.06). Post natal age has significant association with TcB (p value 0.01) and TSB (p value 0.031). Requirement of phototherapy in both group were also significant (p value <0.001). TcB value of 11 mg/dl was chosen as cut off point corresponding TSB level 13 mg/dl with sensitivity 90% and specificity 71%. Above this level indicate need for blood sampling to take appropriate therapeutic measure. Conclusion: Transcutaneous billirubinometry is a non-invasive and valid screening tool for assessing jaundice in newborn. Bangladesh J Child Health 2015; VOL 39 (3) :116-122